Cocoa climate risk assessment tool: Site specific guidance on climate change in cocoa areas - Castaño, Silvia-Elena; Gutierrez, Natalia; Castro, Fabio; Bunn, Christian (2024)
Adaptation to climate change is site specific. Climate impacts are not uniform, they differ by the degree and quality of hazards. This tool allows you to conduct a rapid assessment of climatic changes in cocoa zones to guide interventions. First, you will learn about changes already manifest to date, then about future climate projections. Anticipatory adaptation is first guided by the degree of impact, then by an analysis of most likely climatic changes. Last, deforestation is the main source of emissions in the cocoa sector. Therefore you can assess the importance of deforestation events in regions of interest as a last step. Site specific guidance on climate change in cocoa areas. Main results disseminated through the ArcGIS Storymap App https://csi.maps.arcgis.com/apps/Cascade/index.html?appid=1813b61d6aff4babb803c4322fc12f09 (English)